(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2004)
Zen Buddhism was introduced to China in the sixth century. After going through a long process in China, finally Zen came to Japan in the thirteenth century brought by Japanese monks. A unique spiritual genius one of the greatest epoch-making events in the history of mankind, which in the course of time has come to enrich the human mind over many centuries. During the process of spreading of Zen Buddhism there were influences experienced by two Chinese great religions, Tao and Confucian. This study will discuss the philosophy and architectural aspects of the Zen monastery arrangement plan. Zen Buddhism is syncretism from Taoism and Confucianism.The layout plan of the Zen monastery temple principally was placed on a single axis and facing south. The typical layout plan was borrowed from the architecture of the Chinese monastery.